Artificial Intelligence-Based Mathematics Learning Media Integrated With Islamic Values: What’re The Experts Think About? - Kharisma, Nafilah Ulfah; Nursupiamin, Nursupiamin; Elfira, Riska (Koordinat Jurnal MIPA, 2025)
This study aims to develop an Islamic-integrated mathematics learning media based on Artificial Intelligence (AI), with the expectation of enhancing learning effectiveness in the digital era. The research employed the ADDIE development model, which consists of the stages of analysis, design, and development. The participants in this study were three experts who validated the developed media, named "SAFINAH." The instruments used included validation sheets based on a Likert scale to assess the validity aspects of the media, both in terms of content and appearance. Data collection techniques involved expert evaluations, while data analysis was conducted by calculating the percentage of validity scores. The results showed that the "SAFINAH" media achieved a validity score above 88%, categorized as very valid, indicating that the media is suitable for use in the learning process. The impact of this study is expected to contribute to educational innovation by integrating Islamic values with AI-based technology and encourage the creation of more interactive learning media that align with students’ needs in the digital age